The arms race between bacteria CBASS and bacteriophages - Wang, Lan; Zhang, Leiliang (Frontiers in Immunology, 2023)
The Bacterial Cyclic oligonucleotide-Based Anti-phage Signaling System (CBASS) is an innate immune system that induces cell suicide to defend against phage infections. This system relies on cGAS/DncV-like nucleotidyltransferases (CD-NTase) to synthesize cyclic oligonucleotides (cOs) and CD-NTase-associated proteins (Caps) to execute cell death through DNA cleavage, membrane damage, and NAD depletion, thereby inhibiting phage replication. Ancillary proteins expressed in CBASS, in combination with CD-NTase, ensure the normal synthesis of cOs and prepare CD-NTase for full activation by binding to phage genomes, proteins, or other unknown products. To counteract cell death induced by CBASS, phage genes encode immune evasion proteins that curb Cap recognition of cOs, allowing for phage replication, assembly, and propagation in bacterial cells. This review provides a comprehensive understanding of CBASS immunity, comparing it with different bacterial immune systems and highlighting the interplay between CBASS and phage. Additionally, it explores similar immune escape methods based on shared proteins and action mechanisms between prokaryotic and eukaryotic viruses.